( | 2 | − | x | ) | ( | 2 | − | x | ) | ÷ | 4 | = | 5 |
Left side of the equation = | 2 | ( | 2 | − | x | ) | × | 1 4 | − | x | ( | 2 | − | x | ) | × | 1 4 |
= | 1 2 | ( | 2 | − | x | ) | − | x | ( | 2 | − | x | ) | × | 1 4 |
= | 1 2 | × | 2 | − | 1 2 | x | − | x | ( | 2 | − | x | ) | × | 1 4 |
= | 1 | − | 1 2 | x | − | x | ( | 2 | − | x | ) | × | 1 4 |
= | 1 | − | 1 2 | x | − | x | × | 2 | × | 1 4 | + | x | x | × | 1 4 |
= | 1 | − | 1 2 | x | − | x | × | 1 2 | + | x | x | × | 1 4 |
= | 1 | − | 1 | x | + | x | x | × | 1 4 |
1 | − | 1 | x | + | x | x | × | 1 4 | = | 5 |